2016
DOI: 10.1038/srep38751
|View full text |Cite
|
Sign up to set email alerts
|

Protective role for lipid modifications of Src-family kinases against chromosome missegregation

Abstract: Src-family tyrosine kinases, which are expressed in various cell types, play critical roles in cell signalling at the cytoplasmic side of the plasma membrane through their lipid modifications. Src-family kinases are cotranslationally myristoylated and posttranslationally palmitoylated in the amino-terminal region. The Src-family member Lyn contains a myristoylation site at glycine-2 and a palmitoylation site at cysteine-3, whereas c-Src has a myristoylation site at glycine-2 but not any palmitoylation sites. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Cells exhibit chromosome instability through abnormal chromosome segregation in the next cell cycle of tetraploid cells. v-Src-induced chromosome bridge formation also contributes to the chromosome instability (7,25,44). The chromosome instability generates genetic diversity, and cells capable of adapting to growth-suppressive conditions by anti-cancer drugs or cells gaining metastatic ability can be selected (7).…”
Section: V-src Induces Mitotic Slippage Through Cdk1 Phosphorylationmentioning
confidence: 99%
“…Cells exhibit chromosome instability through abnormal chromosome segregation in the next cell cycle of tetraploid cells. v-Src-induced chromosome bridge formation also contributes to the chromosome instability (7,25,44). The chromosome instability generates genetic diversity, and cells capable of adapting to growth-suppressive conditions by anti-cancer drugs or cells gaining metastatic ability can be selected (7).…”
Section: V-src Induces Mitotic Slippage Through Cdk1 Phosphorylationmentioning
confidence: 99%
“…To synchronize cells at the G 1 /S boundary, a double thymidine block was performed as described 20 , 38 , 39 . In brief, cells treated with 4 mM thymidine for 16 h were incubated in thymidine-free complete medium for 9 h, and the cells were further treated with 4 mM thymidine for 16 h.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysates were prepared in SDS-sample buffer were separated by SDS-PAGE and electrotransferred onto polyvinylidene difluoride membranes (PVDF, Millipore). Immunodetection was performed as reported previously 20 , 34 , 36 , 43 . Sequential reprobing of membranes with a variety of antibodies was performed after the complete removal of primary and secondary antibodies from membranes in stripping buffer or inactivation of horseradish peroxidase by 0.1% NaN 3 , according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The authors found that, upon palmitoylation, Rif1 reduced the silencing of chromatin by competing with Silent Information Regulator/Repressor Activator Protein 1 (SIR/RAP1) complex for telomeric DNA binding. Thereby, Rif1palmitoylation may influence telomere anchoring, nuclear organization, and heterochromatin silencing [91]. Collectively, experimental evidence indicates that protein palmitoylation can be modulated by metabolic signals and may represent a novel mechanism regulating chromatin structure and gene expression.…”
Section: Palmitoylation Of Chromatin Remodelers and Histone Proteinsmentioning
confidence: 99%